Adaptive Weight Estimator for Quantum Error Correction in a Time‐Dependent Environment (Adv. Quantum Technol. 1/2018). Issue 1 (24th August 2018) - Spitz, Stephen T.; Tarasinski, Brian; Beenakker, Carlo W. J.; O'Brien, Thomas E.
Abstract : To execute algorithms on a quantum computer, one must prevent the accumulation of errors by monitoring and correcting them in control hardware. Repetition code and error correction are discussed by Stephen T. Spitz et al. in article number1800012 : To prevent collapse of the protected logical state, quantum error correction requires non‐local parity checks. Errors cause correlated non‐trivial results from these checks, which are matched to determine the underlying system state.